Impaired structural hippocampal plasticity is associated with emotional and memory deficits in the olfactory bulbectomized rat - Morales-Medina, J.C.; Juarez, I.; Venancio-García, E.; Cabrera, S.N.; Menard, C.; Yu, W.; Flores, G.; Mechawar, N.; Quirion, R. (Neuroscience, 2013)
► OBX increases hyperlocomotion in the open field test. ► OBX induces immobility in the forced swim test. ► OBX disrupts spatial memory acquisition in the Morris water test. ► OBX rearranges neuronal arborization in the hippocampus and piriform cortex. ► OBX decreases the number of proliferative cells in the hippocampus. Disturbances in olfactory circuitry have been associated with depression in humans. The olfactory bulbectomized (OBX lesion) has been largely used as a model of depression-like behavior in the rat. However, quantitative neuronal rearrangements in key brain regions in this animal model have not been evaluated yet. Accordingly, we investigated changes in hippocampal plasticity as well as behavioral deficits in this animal model. OBX-induced behavioral deficits were studied in a battery of tests, namely the open field test (OFT), forced swim test (FST), and spatial memory disturbances in the Morris water maze (MWM). To characterize the neuronal remodeling, neuroanatomical rearrangements were investigated in the CA1 hippocampus and piriform cortex (PirC), brain regions receiving inputs from the olfactory bulbs and associated with emotional or olfactory processes. Additionally, cell proliferation and survival of newborn cells in the adult dentate gyrus (DG) of the hippocampus were also determined. OBX induced hyperlocomotion and enhanced rearing and grooming in the OFT, increased immobility in the FST as well as required a longer time to find the hidden platform in the MWM. OBX also induced dendritic atrophy in the hippocampus and PirC. In addition, cell proliferation was decreased while the survival remained unchanged in the DG of these animals. These various features are also observed in depressed subjects, adding further support to the validity and usefulness of this model to evaluate potential novel antidepressants.